Improved Retinal Microcirculation After Cardiac Surgery in Patients With Congenital Heart Disease - Cong Li; Cong Li; Zhuoting Zhu; Haiyun Yuan; Pingting Zhong; Pingting Zhong; Qingsheng Peng; Qingsheng Peng; Xinran Dong; Manqing Huang; Baoyi Liu; Baoyi Liu; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Microcirculatory changes in congenital heart disease (CHD) patients undergoing cardiac surgery are not fully understood. We aimed to investigate the changes of retinal microcirculation in CHD patients after cardiac surgery by optical coherence tomography angiography (OCTA) and explore the association between retinal microcirculation and surgical outcome.Methods: This prospective observational study consisted of 71 CHD patients aged ≥6 years undergoing cardiac surgery including 19 cyanotic CHD (CCHD) and 52 acyanotic CHD (ACHD). Optical coherence tomography angiography (OCTA) was used to measure vessel density (VD) and capillary density (CD) of radial peripapillary capillary (RPC) and peripapillary, VD of superficial capillary plexus (SCP) and deep capillary plexus (DCP), thickness of retinal nerve fiber layer (RNFL) and ganglion cell complex (GCC) preoperatively and 1 month postoperatively. Transthoracic echocardiography was conducted to measure macrocirculation.Results: In CCHD patients, VD and CD of RPC and peripapillary increased postoperatively (all P < 0.05). In ACHD patients, VD of peripapillary, CD of RPC and peripapillary, and RNFL thickness increased postoperatively (all P < 0.05). VD of SCP and DCP, and GCC thickness did not change significantly in CHD patients after surgery. Lower preoperative retinal microvascular density was associated with longer cardiopulmonary bypass (CPB) time and postoperative length of stay (PLOS). No correlation was found between microcirculatory and macrohemodynamic parameters (all P > 0.05).Conclusions: Improved retinal microcirculation was observed after congenital cardiac surgery and impaired preoperative retinal microvasculature was associated with prolonged CPB time and PLOS, which might provide potential information about the outcome of congenital cardiac surgery.